Design of a high power PIN‐diode controlled switchable RF transmit array for TRASE RF imaging. Issue 1 (7th June 2018) - Der, Eric; Volotovskyy, Vyacheslav; Sun, Hongwei; Tomanek, Boguslaw; Sharp, Jonathan C.
Abstract: Some MRI applications require the generation of a series high power RF pulses in which the spatial transmit B1 field pattern over the sample is modified between one pulse and the next. This requirement may be realized by a RF transmit array with the capability to enable and disable individual elements to switch between field patterns with switching times of the order 10 μs. Our application is for a TRASE ("Transmit Array Spatial Encoding") array for which short high power pulses are necessary to achieve high resolution (mm‐level) spatial encoding. We present designs for coil array, coil switching circuits, and a high power PIN diode driver together capable of robust and rapid switching of short (~120 μs) high power pulses for a 24 cm TRASE phase gradient coil suitable for imaging extremities at 8 MHz. We describe in detail the selection of suitable coil components and switch circuit designs to satisfy a specific requirement for maximum B1 field strength, and provide all circuit designs.